Psychological Resilience Enhances the Orbitofrontal Network in the Elderly With Mild Cognitive Impairment - Son, Sang Joon; Park, Bumhee; Choi, Jin Wook; Roh, Hyun Woong; Kim, Na-Rae; Sin, Jae Eun; Kim, Haena; Lim, Hyun Kook; Hong, Chang Hyung (Frontiers in Psychiatry, 2019)
Background: It has been suggested that maintaining the efficient organization of the brain’s functional connectivity (FC) supports neuroflexibility under neurogenerative stress. This study examined psychological resilience related FC in one hundred twelve older adults with mild cognitive impairment. Methods: Using a resting-state functional magnetic resonance imaging (fMRI) approach, we investigated reorganization of the orbitofrontal gyrus (OFG)/ amygdala (AMG)/ hippocampus (HP)/ parahippocampal gyrus (PHG) FC according to the different level of resilience scale. Results: Compared with the low resilient group, the high resilient group had greater connectivity strengths between the left inferior OFG and right superior OFG (P<0.05, Bonferroni corrected), between the right inferior OFG and left PHG (P<0.05, Bonferroni corrected), and between the right middle OFG and left PHG (False Discovery Rate<0.05). Conclusion: Psychological resilience may be associated with enhancement of the orbitofrontal network in the elderly with MCI.